2021
DOI: 10.1111/jog.14579
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and gynecological cancers: Asia and Oceania Federation of Obstetrics and Gynecology oncology committee opinion

Abstract: Since the outbreak of COVID‐19, there have already been over 26 million people being infected and it is expected that the pandemic will not end in near future. Not only the daily activities and lifestyles of individuals have been affected, the medical practice has also been modified to cope with this emergency catastrophe. In particular, the cancer services have faced an unprecedented challenge. While the services may have been cut by the national authorities or hospitals due to shortage of manpower and resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Keeping in mind that gyne-oncology accounts not only for 35.1% of overall gynecology patients (GYN* 1 ) but also for 52.9% of the department’s revenue generation (GYN* 2 ), the feared medical damage relating to diagnostics and treatment delays, failing screening procedures, and related worsened treatment outcome is accompanied with a possibly fierce recess in the economic performance. While the data expand previous observations by confirming the total patient number of gyne-oncology to decrease for the whole COVID-19 pandemic, it depicts a varying effect on the specific malignant main diagnoses [ 9 , 10 , 14 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Keeping in mind that gyne-oncology accounts not only for 35.1% of overall gynecology patients (GYN* 1 ) but also for 52.9% of the department’s revenue generation (GYN* 2 ), the feared medical damage relating to diagnostics and treatment delays, failing screening procedures, and related worsened treatment outcome is accompanied with a possibly fierce recess in the economic performance. While the data expand previous observations by confirming the total patient number of gyne-oncology to decrease for the whole COVID-19 pandemic, it depicts a varying effect on the specific malignant main diagnoses [ 9 , 10 , 14 , 30 ].…”
Section: Discussionsupporting
confidence: 80%
“…The visualization of the relative monthly development of patient numbers leads to the following observations that expand the previous scientific status quo [ 9 , 10 , 12 , 14 , 16 , 30 ]. Obstetric care appears to not have been affected to a large extent by the effects of the COVID-19 pandemic in terms of admitted cases at Marburg University Hospital, this expands the finding to the second year of the pandemic [ 12 ].…”
Section: Discussionmentioning
confidence: 72%
“…These effects has been sufficiently severe that some consider the screening programs for this disease to be in a state of crisis [8][9][10]. Other studies have also shown an increasing number of women diagnosed with premalignant lesions [11][12][13]. Although many reasons may explain these negative effects, the decreased number of patients undergoing screening may be part of the problem [10,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…1 There have been occasions when it was necessary for treatment to deviate from what would be considered standard of care, due to clinical resource availability, increased risk from COVID-19 infection and prioritisation frameworks. [2][3][4][5][6][7] In the international COVIDSurg study, 17% of 4722 women undergoing surgery for gynaecological cancer had alteration in first line treatment, including treatment delay or adaptation of surgery. 8 In the United Kingdom, the COVID-19 pandemic severely impacted on gynaecological cancer services resulting in the need for prioritisation of care 1 .…”
Section: Introductionmentioning
confidence: 99%